Identification of Tumor Initiating Cells with a Small‐Molecule Fluorescent Probe by Using Vimentin as a Biomarker. (14th February 2018) - Lee, Yong‐An; Kim, Jong‐Jin; Lee, Jungyeol; Lee, Jia Hui Jane; Sahu, Srikanta; Kwon, Haw‐Young; Park, Sung‐Jin; Jang, Se‐Young; Lee, Jun‐Seok; Wang, Zhenxun; Tam, Wai Leong; Lim, Bing; et al.
Abstract: Tumor initiating cells (TICs) have been implicated in clinical relapse and metastasis of a variety of epithelial cancers, including lung cancer. While efforts toward the development of specific probes for TIC detection and targeting are ongoing, a universal TIC probe has yet to be developed. We report the first TIC‐specific fluorescent chemical probe, TiY, with identification of the molecular target as vimentin, a marker for epithelial‐to‐mesenchymal transition (EMT). TiY selectively stains TICs over differentiated tumor cells or normal cells, and facilitates the visualization and enrichment of functionally active TICs from patient tumors. At high concentration, TiY also shows anti‐TIC activity with low toxicity to non‐TICs. With the unexplored target vimentin, TiY shows potential as a first universal probe for TIC detection in different cancers.